ANALISIS PEMAKNAAN PEMUSTAKA ATAS RUANG PERPUSTAKAAN FEB UNDIP - Endang Fatmawati (VISI PUSTAKA: Buletin Jaringan Informasi Antar Perpustakaan, 2016)
This study is inspired by the change in the concept of the traditional library space to a modern facility. The concept of definition in this study is aimed at explaining how library users mark and define spaces within Diponegoro University Economy and Business Faculty Library. This new ethnography method is used to obtain a comprehensive description by conducting a critical analysis of users' defining practice toward the spaces provided in the library. Data is collected by observing participants, interviews and literature review. There are four informants chosen purposively. The result shows that the library is defined as a comfortable place for using the Internet, spending free times, a place for intellectuals. The result is therefore usedfor  constn1cting the identity of users with modern lifestyles.